Estudos sobre expressão gênica em células germinativas e somáticas: indicadores moleculares da fertilidade e efeitos de dietas hiperlipídicas - Souza, Alethéia Carízia Baracho de Lima (2014)
This thesis presents two chapters. In the first chapter, its objective was to investigate the potential use of correlative microarray-based transcript pairs as candidate markers for male fertility using dysplasia of the fibrous sheath (DFS) as an affected model. It is widely recognized that microarray technology may be limited by cost and that the quality of the transcript remains relatively unknown. To address these issues, we analyzed the stable transcript pairs by qPCR with a systematic primer design process. On this experimental study, we used men with proven fertility and men with a diagnosis of DFS. Our approach was based on primer sequences for six genes of interest were designed using Oligo7 and Primer3Plus. Primer specificity was initially assessed in silico by searching the ENSEMBL, University of California Santa Cruz, and National Center for Biotechnology Information databases for nontarget complementary sequences throughout the genome. The ability of transcript pairs to classify samples from males of proven fertility away from DFS was assessed. Our results showed that in conjunction with identifying four new stable transcript pairs, comparison of the DFS qPCR C(t) correlation coefficients revealed the disruption of four stable fertile sample transcript pairs. This suite of transcript pairs resolves DFS. In conclusion, the results show that with effectively designed primers, qPCR may provide an affordable molecular assay to assess male fertility status. Second chapter includes two studies regarding evaluations of ram feeded with supplemented diet with cashew nut. On the frist study, our goal was detect transcripts for Heat Shock Protein (HSP70), Clusterin (CLU), Ovis aries T-complex protein 1 alfa subunit-like protein (TCP1) e Ovis aries chaperonin containing TCP1, subunit 8 (theta) (CCT8) on ram sperm by. For primer designing we used published ESTs from NCBI and manually annotated by us using Primer3Plus and OligoAnalizer. PRM2 was used as internal qPCR control. Semen samples from mature Morada Nova ram were collected by eletroejaculator, washed in PBS and prepared for further RNA extraction. Selected samples followed quality recommendatios from Colégio Brasileiro de Reprodução Animal regarding motility, vigor and concentration. Our results showed presence of mRNA HSP70 on ram sperm and they can possible be envolved in early embryo development, oocyte activation and post fertilization events. Further analyses will be necessary to confirm presence of TCP1 and CCT8 on ram sperm. Our findings indicate new perpectives about the effects of these chaperones during embryo development mesuring if its expression reflects male fertility on the early embryo development. On the second study the the main goal is to evaluate the effects of a lipid-enriched diet containing cashew nut brain on the expression of genes related to lipid metabolism in the longissimus dorsi muscle of Morada Nova rams. Twenty sexually mature and reproductively sound rams were divided in two groups based on ram live weight, and each ram was kept on individual pens. During three months, group 1 (G1) rams were fed with a lipid-rich diet, containing cashew nut bran (CNB), while group 2 (G2) was fed with a meal based on corn and soy. Both diets were isocaloric and isoproteic, and had a mineral mix added-in. The rams also were offered Tifton grass hay and had free access to water. The amount of diet offered (ration plus hay) was adjusted everyday to a maximum waste of 10%. Seven genes coding for proteins directly or indirectly involved in lipid metabolism were initially selected as targets, incluiding GH, ACACA, CAST, CAPN3, LPL, SCD, and FASN. Also, five genes were selected as reference genes, ACTB, GAPDH, RPL4, RPS18 and TBP. From the seven genes originally selected as targets, GH, ACACA and CAST were removed, leaving the final list with four targets. The first two genes were removed due to alternative pairing of the primers (low specificity), while CAST showed low amplification efficiency during PCR reaction. From the final target list, the expression of only two genes was affected by diet, SCD (p<0.01) and FASN (p<0.05), while LPL (p=0,1022) and CAPN3 (p=0,0939) were not different at the p<0.05 level. Both SCD and FASN genes were down-regulated in G1 (lipid-rich diet containing CNB) compared to G2. These genes are involved in lipogenic pathways, related to tissue lipid deposition; therefore, these results were expected. This is the first time that a fat-rich diet based on CNB was shown to affect gene expression of proteins involved in fat deposition in carcass muscles of rams. Longissimus dorsi is one of the finest meat cuts. Considering that human diets rich in poli-unsaturated fatty acids (PUFA) can decrease the risk of heart and other chronic diseases, a change in the fatty acid profile of this muscle could contribute to a healthier diet, aggregating value to the end-product of the lamb meat market. The effects of CNB-based diet on the gene expression of SCD and FASN support the notion that such diet, as previously shown for other sources of lipid in ruminants, can potentially change the fatty acid composition of L. dorsi, but this hypothesis needs to be experimentally verified by profiling fatty acids in animals fed CNB versus carbohydrate-based diets. CNB use as an ingredient in animal feeding is environmentally-friendly, since it contributes to by-product recycling from the agroindustrial plants in Northeast Brazil. Also, considering that CNB-based diet changes lipogenic gene expression without affecting weight gain or reproductive status of the rams, as shown in another work from our team, makes CNB a very important alternative food in ram production systems in tropical regions.